The Role and Significance of Chorus in National Opera - Rayetovich, Gafarov Ruslan (Research Parks Publishing LLC, 2023)
The article highlights the flowering of opera and choral art in Uzbekistan. Choral scenes in opera, which are the main means of musical dramaturgy, are important and occupy a very large place. People in opera are the main actors, many choruses and choral scenes, show genuine sincerity in expressing emotions and enliven the scene. The aim of the article is to reveal the role and importance of the chorus in the comprehensive development of Uzbek opera.